2006
DOI: 10.1016/j.neuron.2006.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Vesicles Interchange Their Membrane Proteins with a Large Surface Reservoir during Recycling

Abstract: During recycling of synaptic vesicles (SVs), the retrieval machinery faces the challenge of recapturing SV proteins in a timely and precise manner. The significant dilution factor that would result from equilibration of vesicle proteins with the much larger cell surface would make recapture by diffusional encounter with the endocytic retrieval machinery unlikely. If SV proteins exchanged with counterparts residing at steady state on the cell surface, the dilution problem would be largely avoided. In this scena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
196
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(220 citation statements)
references
References 24 publications
23
196
0
1
Order By: Relevance
“…Two recent studies found evidence for the existence of a pool of synaptic vesicle proteins on the plasma membrane that is selectively and readily retrieved after brief or mild stimuli (49,50). Partially preassembled endocytic structures waiting to be recovered after a stimulus could, in principle, account for the rapid endocytosis elicited under some conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies found evidence for the existence of a pool of synaptic vesicle proteins on the plasma membrane that is selectively and readily retrieved after brief or mild stimuli (49,50). Partially preassembled endocytic structures waiting to be recovered after a stimulus could, in principle, account for the rapid endocytosis elicited under some conditions.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are mobile and intermix with newly exocytosed synaptic vesicle proteins 44,45 . By contrast, super-resolution stimulated emission depletion (STED) microscopy (BOX 4) has suggested that newly exocytosed synaptic vesicle proteins are clustered at the plasma membrane 46 .…”
Section: Box 1 | Presynaptic Organization -Exocytic and Endocytic Zonesmentioning
confidence: 99%
“…This apparent contradiction could be explained by differences between pHluorin-tagged synaptic vesicle membrane proteins and their native endogenous counterparts 47 . Alternatively, synaptic vesicle proteins may undergo postexocytic reclustering within the periactive zone 44,45 (FIG. 4), a process that could become rate-limiting under conditions of sustained activity (see below).…”
Section: Box 1 | Presynaptic Organization -Exocytic and Endocytic Zonesmentioning
confidence: 99%
See 1 more Smart Citation
“…This construct has been extensively used to investigate synaptic vesicle properties within hippocampal neurons in vitro Ryan, 2000, 2001;Fernandez-Alfonso et al, 2006) and at Drosophila (Poskanzer et al, 2003;Reiff et al, 2005) and mouse (Tabares et al, 2007) neuromuscular junctions in vivo. The pH shift that occurs during exocytosis, when the acidic vesicle interior is exposed to the neutral extracellular space, leads to an increase in spH fluorescence.…”
Section: Introductionmentioning
confidence: 99%